A Review on Removal of Heavy Metal Ions from Waste Water using Natural/ Modified Bentonite - Prabhu Prathiksha P.; Prabhu Balakrishna (MATEC Web of Conferences, 2018)
The pollution of water due to various toxic components especially heavy metals are causing an adverse effect on the flora and fauna and also have a potential effect on the human well-being. Due to this there is an immediate requirement to find various techniques for the removal of lethal toxins in wastewater. Amongst all of the existing methods, adsorption is one of the most effective and efficient technique for the elimination of contaminants such as heavy metals from wastewater. The increasing number of research publications on adsorption of heavy metals using modified bentonite leads to the fact that there has been a surging importance in the production of a variety of economical adsorbents for water treatment. Outcome from the latest advances in using bentonites and modified bentonite shows the adaptable nature of the clay and its environment friendly nature. The present review shows the removal of heavy metals using modified bentonite. The main purpose of this review is to describe the flexible way of natural bentonite and modified bentonite and its ability to absorb array of inorganic pollutants, which are present in the waste water. It is apparent from the review that modified bentonite have displayed high removal potential for certain kind of inorganic contaminants from wastewater.